Encyclopedia of gender in media - Kosut, Mary (Sage Reference, 2012)
The media strongly influences our everyday notions of gender roles and our concepts of gender identity. The Encyclopedia of Gender in Media critically examines the role of the media in enabling, facilitating, or challenging the social construction of gender in our society. The work addresses a variety of entertainment and news content in print and electronic media and explores the social construction of masculinity as well as femininity. In addition to representations of gender within the media, we also analyze gender issues related to media ownership and the media workforce. Despite an abundance of textbooks, anthologies, and university press monographs on the topic of gender in media, until now no comprehensive reference work has tackled this topic of perennial interest in student research and papers.Features & Benefits:150 signed entries (each with Cross References and Further Readings) are organized in A-to-Z fashion to give students easy access to the full range of topics within gender in media.A thematic Reader’s Guide in the front matter groups related entries by broad topical or thematic areas to make it easy for users to find related entries at a glance, with themes including "Discrimination & Media Effects," "Media Modes," "New Media," "Media Portrayals & Representations," "Biographies," and more.In the electronic version, the Reader's Guide combines with a detailed Index and the Cross References to provide users with robust search-and browse capacities.A Chronology in the back matter helps students put individual events into broader historical context.A Glossary provides students with concise definitions to key terms in the field.A Resource Guide to classic books, journals, and web sites (along with the Further Readings accompanying each entry) helps guide students to further resources for their research journeys.An Appendix provides users with a number of reports related to gender in media.